Deficiency of CCN5/WISP-2-Driven Program in breast cancer Promotes Cancer Epithelial cells to mesenchymal stem cells and Breast Cancer growth - Amlan Das (Nature Portfolio, 2017)
Abstract Breast cancer progression and relapse is conceivably due to tumor initiating cells (TICs)/cancer stem cells. EMT (epithelial-mesenchymal-transition)-signaling regulates TICs’ turnover. However, the mechanisms associated with this episode are unclear. We show that, in triple-negative-breast cancer (TNBC) cells enriched with TICs, CCN5 significantly blocks cellular growth via apoptosis, reversing EMT-signaling and impairing mammosphere formation, thereby blocking the tumor-forming ability and invasive capacity of these cells. To corroborate these findings, we isolated tumor-initiating side populations (SP) and non-side population (NSP or main population) from MCF-7 cell line, and evaluated the impact of CCN5 on these subpopulations. CCN5 was overexpressed in the NSP but downregulated in the SP. Characteristically, NSP cells are ER-α positive and epithelial type with little tumorigenic potency, while SP cells are very similar to triple-negative ones that do not express ER-α- and Her-2 and are highly tumorigenic in xenograft models. The overexpression of CCN5 in SP results in EMT reversion, ER-α upregulation and delays in tumor growth in xenograft models. We reasoned that CCN5 distinguishes SP and NSP and could reprogram SP to NSP transition, thereby delaying tumor growth in the xenograft model. Collectively, we reveal how CCN5-signaling underlies the driving force to prevent TNBC growth and progression.